2004
DOI: 10.1079/bjn20041022
|View full text |Cite
|
Sign up to set email alerts
|

Intake of dietary iron is low in patients with Crohn's disease: a case–control study

Abstract: Patients with Crohn's disease (CD) often experience Fe deficiency (ID) and frequently alter their diet to relieve abdominal symptoms. The present study set out to assess whether patients with CD have dietary habits that lead to low Fe intakes and/or reduced bioavailable Fe compared with control subjects. Patients with asymptomatic CD were matched to controls (n91/group). Dietary intakes of Fe and contributions from different food groups were compared using a 7 d food diary. Promoters and inhibitors of non-haem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
70
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(76 citation statements)
references
References 41 publications
5
70
0
1
Order By: Relevance
“…In addition, several studies demonstrated that oral iron induces oxidative stress in the gut and aggravates inflammation [11,27]. In IBD patients, there is often the need for high iron doses due to very low iron stores, resulting from chronic bleeding or inflammatory conditions [2,28,29]. …”
Section: Discussionmentioning
confidence: 99%
“…In addition, several studies demonstrated that oral iron induces oxidative stress in the gut and aggravates inflammation [11,27]. In IBD patients, there is often the need for high iron doses due to very low iron stores, resulting from chronic bleeding or inflammatory conditions [2,28,29]. …”
Section: Discussionmentioning
confidence: 99%
“…The causes are multi-factorial with Fe deficiency and anaemia of chronic disease being the most common. Poor dietary Fe intakes (36) through avoidance of Fe-rich foods due to food aversions or intolerances may contribute to ongoing Fe deficiency but they are unlikely to be the only contributing factor to the anaemia in IBD (50) . In IBD, inflammation, Fe deficiency and anaemia of chronic disease often co-exist, making assessment of Fe status complex.…”
Section: Anaemiamentioning
confidence: 99%
“…Iron deficiency anemia is the most prevalent cause for anemia in IBD, with an estimated prevalence of 36-76% depending on the population (outpatient vs. inpatient) [4,5] . Iron deficiency may be a consequence of dietary restrictions, malabsorption, or intestinal bleeding [6][7][8] .…”
Section: Introductionmentioning
confidence: 99%